Weed management in conservation agriculture based soybean-wheat cropping system - M, Raghavendra; Billore, S D; Singh, Y V; Ramesh, A; Verma, Rakesh K; Halli, Hanamant M; Hatti, Veeresh; Goud, B R (Indian Farming, 2020)
Soybean-wheat is one of the dominant cropping systems of India. In recent years, productivity of soybean-wheat system is decreasing due to biotic and abiotic stresses. Hence, adaptation of conservation agriculture practices in soybeanwheat system will enhance the productivity of cropping system. Weed management is one of the crucial components of conservation agriculture due to non availability of labour, frequent rains for kharif crop, residue retention interference narrow down use of pre-plant and preemergent herbicides in both crops under CA system. Therefore, availability of prominent broad spectrum post emergent herbicides either alone or tank mixture with other herbicide or factory mixture for successful control of grassy, sedges and broad leave weeds along with herbicide resistant weeds in soybeanwheat cropping system will further encourages to adopt CA practice to enhance yield and obtain higher profit to farmers under conservation agriculture based soybean-wheat cropping system.